Measurement of Outside Thread Pitch Distance Results of TONGTAI TCS 1500[M] CNC Lath Using Profile Projector - Jaja Miharja; Heru Santoso; Hery Adrial; Muhamad Japar (Prodi Teknik Mesin, 2021)
Research has been carried out on the Measurement of the Outer Thread Pitch Distance from the Tongtai Tcs 1500[M] Cnc Lathe Using a Projector Profile. The use of a screw system to unite two components, is almost always found in all industrial technology results from the form of industrial technology with a low level of accuracy (rough) to a very high level of precision (precision). Therefore the screw system has become one of the important factors in industrial progress in all types of production. The higher the level of a component made means the higher the level of accuracy of the thread system. In this study, calculations were carried out to determine the level of precision of a thread made through the machining process using a TONGTAI TCS 1500 [M] CNC lathe. The precision measurement was carried out by measuring using a dimension measuring instrument, namely Profile Projector type HST-CPJ-3000/3000Z. To find out the average value and the value of the screw deviation, a research and measurement process was carried out with several product samples or test objects (sample A, sample B, sample C) where each sample was the same size, namely M15 × 50 P 1.5. The first measurements were made on the major and minor diameters. Because this measurement is more focused on the level of precision of the thread pitch distance, the second measurement is carried out by measuring the dimensions of the distance between the pitches as much as N = 10. From the 10 measuring points of the thread pitch distance, different average values and deviation values will be produced although in the same size.. The purpose of this study was to determine the level of pressure of a thread made through a machining process which in this study used a CNC TONGTAI TCS 1500 [M] lathe. it is known that the overall average value of the three samples is with a major diameter = 14,949 mm, a minor diameter = 13,219 mm, and a thread pitch distance = 1.5309 mm.